High-Frequency Repetitive Magnetic Stimulation Activates Bactericidal Activity of Macrophages via Modulation of p62/Keap1/Nrf2 and p38 MAPK Pathways - Therese B. Deramaudt; Ahmad Chehaitly; Théo Charrière; Julie Arnaud; Marcel Bonay (MDPI AG, 2023)
The effects of repetitive magnetic stimulation (rMS) have predominantly been studied in excitable cells, with limited research in non-excitable cells. This study aimed to investigate the impact of rMS on macrophages, which are crucial cells in the innate immune defense. THP-1-derived macrophages subjected to a 5 min session of 10 Hz rMS exhibited increased Nrf2 activation and decreased Keap1 expression. We found that activation of the Nrf2 signaling pathway relied on rMS-induced phosphorylation of p62. Notably, rMS reduced the intracellular survival of Staphylococcus aureus in macrophages. Silencing Nrf2 using siRNA in THP-1-derived macrophages or utilizing Nrf2 knockout in alveolar macrophages abolished this effect. Additionally, rMS attenuated the expression of IL-1β and TNF-α inflammatory genes by S. aureus and inhibited p38 MAPK activation. These findings highlight the capacity of rMS to activate the non-canonical Nrf2 pathway, modulate macrophage function, and enhance the host's defense against bacterial infection.